POPULATION MONITORING AND MAJOR THREATS TO DEMOISELLE CRANE(GRUS VIRGO) AT LASBELA COAST, BALOCHISTAN, PAKISTAN - Sehrish Qayum; Muhsan Ali Kalhoro; Abdul Hakeem; Maqbool Dashti; Atiq-ur-Rehman; Muhammad Shafi (Journal of Animal and Plant Sciences, 2024)
The Demoiselle Crane (Grus virgo) is one of the most threatened bird species in the world as it is indicated as “Least Concern” under the IUCN and BirdLife International category. To evaluate the current status and threats to G. virgo from Lasbela coast, two field stations were selected i.e, Siranda lake and Sonmiani area. Data were based on daily observation monitored during February, March, April, September, October, November, and December during 2020-2021. The line transit method and questionnaire-interview based survey was used to estimate the bird population and threats to birds population. Total of 322,143 numbers of cranes were observed in which 142700 in autumn and 179443 during spring season. Area wise distribution of cranes were detected at 271701 from Sarinda lake while, 50442 cranes were observed from Sonmiani area. It was also noted that during autumn overall 136850 cranes were observed in flying mode while 5850 were observed at resting stage, however in Spring 167330 were in flying and 12113 were at resting. Overall, high population was observed during spring season at 55.7% while population during autumn was observed at 44.29%. It was also noted that during present study the percentage of flying cranes are higher than the resting cranes and higher numbers were observed from Sarinda lake compared to Sonmiani area. This maybe because the Sarinda lake is far from city area so cranes prefer to rest compare to Sonmiani area. The hunting information was collected from local community, government agencies and personal visits at local areas. It was noted that total of 116 numbers of cranes were hunted during the study period from which 74 cranes were hunted using gunshot and 42 cranes were caught alive. Most of the hunting cranes were operated during March. We may assume that these sites (study area) are short term stay for these guest birds. However, due to certain reasons it may also be noted that flying cranes are higher than the resting cranes which shows that these sites also indicate the threats to the cranes. It may also suggest that hunting must be prohibited and Sarinda lake should be declared as Ramsar site for the conservation of migratory birds.
Keywords: Sarinda lake; Siberian crane; Endangered; Hunting; Lasbela; Pakistan